Komunikasi Organisasi Paguyuban Pasar Triwindu Dalam Meningkatkan Pengunjung Di Pasar Triwindu Surakarta - Endrat, Bayu Tresna Setya; Hindra Hastuti, Nurnawati; Sihabuddin, Sihabuddin (Solidaritas, 2024)
Paguyuban Pasar Triwindu is an organization that contains traders in the Triwindu Market. In this Paguyuban Pasar Triwindu have various efforts in increasing visitors to the Triwindu Market post-covid-19 pandemic caused by the coronavirus which resulted in visitors in this market decreased. The aim of this research is to describe how the organization communication efforts of the Paguyuban Pasar Triwindu in increasing visitors to the Triwindu Market. The theory used in this research is the theory of organizational communication introduced by Zelko and Dance which covers internal communication and external communication. This type of research is qualitative descriptive. Determining informants using purposive sampling techniques. Research location on Surakarta Triwindu Market. The results of this research are organizational communication efforts of Paguyuban Pasar Triwindu in improving visitors to the Triwindu Market with Zelko and Dance organizational communications that is at the stage of internal communication, Paguyuban Pasar Triwindu has efforts such as; communication patterns of strategy or planning, media utilization, and evaluation. At the phase of external communication there are efforts in the form of direct communication to visitors and doing cooperation or collaboration with other institutions. Keywords: Paguyuban Pasar Triwindu, Organizational Communication,    Increase Visitor.